The Impact of Intellectual Capital on Bank Profitability during COVID-19: A Comparison with China and Pakistan. (8th February 2022) - Xu, Jian; Haris, Muhammad; Irfan, Muhammad
Abstract : This study aims to examine how the relationship between intellectual capital (IC) and bank profitability changed during COVID-19. Based on the data of 34 Chinese banks and 39 Pakistani banks, this study uses ordinary least squares (OLS) to examine this relationship during the COVID-19 era. Profitability is measured by return on assets (ROA) and return on equity (ROE), and IC is measured by the value added intellectual coefficient (VAIC) model. The findings show that, even during the COVID-19 pandemic, IC has managed to sustain its positive influence on bank profitability in China and Pakistan. Among IC components, our study reports that human capital is the only IC resource that continues to enhance ROA and ROE of Chinese and Pakistani banks during the pandemic period. Our study suggests that policymakers should pay more attention to IC resources, which has the potential to improve banks' profitability even during crisis times.